Study of Types of Tuber Flours and the Addition of Sodium Tripolyphosphate on the Chemical Characteristics of Milkfish Burger Patties (Chanos chanos) - Rusydiana, Indah Nur; Yulistiani, Ratna; Rosida, Dedin Finatsiyatull (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The use of tuber flours (potato flour, taro flour, yellow sweet potato flour), which contains high starch content as a filler, requires the addition of sodium tripolyphosphate (STPP) as a binding agent to improve the characteristics of milkfish burger patties. STPP can reduce product shrinkage, increase water binding capacity, and improve texture. This study aimed to determine the optimal combination of tuber flour type and STPP addition to produce mackerel fish burger patties with the best chemical characteristics. This study used a completely randomized design (CRD) with a factorial pattern consisting of two factors and two replications. Factor 1 was tuber flour (potato flour, taro flour, and yellow sweet potato flour), and Factor 2 was the addition of STPP (0.2%, 0.3%, and 0.4%). Data were analyzed using ANOVA and DMRT post-hoc tests at the 5% level. The best treatment was the use of potato flour and a 0.4% addition of STPP, which produced burger patties made from mackerel fish with a moisture content of 61.66%, an ash content of 2.52%, a protein content of 20.25%, a fat content of 1.58%, and a starch content of 11.05%. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land